What Happens in Home Visits? Examining a Key Parole Activity. (May 2020) - Meredith, Tammy; Hawk, Shila René; Johnson, Sharon; Prevost, John P.; Braucht, George
Home visits provide a space for officer–supervisee encounters. However, little is known about the dynamics of home visits and their association with supervision outcomes. This study examines the context, content, and role of home visits in parole. Home visits are described using systematic observation data of officer-initiated contacts ( N = 383). The average visit included only those on parole, inside a single-family home, lasted 8 minutes, was conducive to discussions, and covered rules and needs topics. A separate agency records dataset ( N = 26, 878) was used to estimate Cox hazard models. Findings suggest that each visit is related to reduced risk of a new felony arrest or a revocation, controlling for criminogenic factors and supervision activities. Risk was further associated with a reduction if officers engaged in mixed-topic discussions (rules and needs). Home visits can enable officers to help people on parole successfully navigate the challenges of reentry.